Racism in Lee Daniels' Movie The Butler (International Journal of Education and Literature, 2022)
The Butler movie explored discrimination between white and black people that created social grade which lead to the conflict. This became a very interesting one to explore. The purpose of this study was to find more about the racism in such movie. The researcher used a qualitative descriptive method, and the research material was a dialogue from the movie "The Butler". The analyse was done by using the theory of racism, "three types of racism”, Michel Wieviorka (1995). The dialogue of the movie accompanied by picture as the sample of the data in analysis done by contextually and theoritically. The result of the study showed attitudes racism was the most prevalent, which means there are discriminations occured to black people in The Butler movie. Attitudes is a pattern of thinking or feeling about something or someone, generally represented in a person's behavior. While prejudice and opinions racism are the most rarely occured in such movie. Prejudice rarely occured in the social life because black people can not express their feeling and they struggle welfare, which was hard to achieve in the movie. Opinions rarely occured in the movie because white people grade was higher than black people in such movie.